Effect of fertilizer application on winter wheat productivity under precision agriculture in Kazakhstan - Alibek Baimuratov; SHOLPAN BASTAUBAYEVA; MEHMET ARSLAN; ZHANAR YERALIYEVA (Society for Indonesian Biodiversity, 2021)
Abstract. Baimuratov, A, Bastaubayeva S, Arslan M, Yeraliyeva Z. 2021. Effect of fertilizer application on winter wheat productivity under precision agriculture in Kazakhstan. Biodiversitas 22: 1558-1563. The effect of mineral fertilization of light chestnut soils of Almalybak, Kazakhstan on the three winter wheat varieties grain yields and NDVI was carried out in 2017/18, 2018/2019 as well as 2019/2020 growing seasons using precision agriculture technologies. The experiments were set up in an incomplete factorial design with rates of NPK N90P60K45, N120P90K60, and N150P120K90. Agrochemical cartograms were ordered for the substance of effectively hydrolyzable nitrogen, extractable phosphorus, and exchangeable potassium. The total variation of NDVI was from 0.62 in the minimum (Bezostaya 100 variety, 2017/18) to 0.88 in the maximum (Aliya variety, 2019/20) in the flowering phase of wheat plants. The highest index of NDVI was observed in the N150P120K90 in the three winter wheat varieties for the three seasons. Studies directed in multivariate analyses built up the connection between fertilizer application, soil fruitfulness, and grain yield. As per the genuine heterogeneity of the fields, standards were determined and differential use of the fundamental phosphorus fertilizer was completed. The yield for the winter wheat varieties varied between 5.6-5.9 t/ha for Aliya variety, 6.5-7.0 t/ha for Grom, and 6.2- 6.7 t/ha for Bezostaya 100, which presents that P120 doses were more suitable in experimental plots for winter wheat varieties. The grain yield on mineral fertilization of NPK for the studied varieties varied from 4.2 to 7.6 t/ha for Aliya variety, from 4.0 to 6.8 t/ha for the Bezostaya 100, and from 4.5 to 7.9 t/ha for Grom. The highest grain yield was observed in the N150P120K90 for three winter wheat varieties in all three seasons.